The Weakness of State Administrative Law as a Catalyst for Corruption in Indonesia: A Juridical Perspective and Proposed Solutions - Anak Agung Gede Agung Indra Prathama (Warmadewa Press, 2025)
From a juridical perspective, the weakness of the State Administrative Law (SAL) system can be regarded as one of the factors that facilitates the occurrence of corruption in Indonesia. The ambiguity of legal norms and the inadequacy of supervisory instruments within the framework of SAL create loopholes for the abuse of power by state officials, which ultimately harms the public interest. Corruption—essentially the misuse of public authority for personal or group gain—often thrives within an administrative system that lacks sufficient principles of efficiency, transparency, and accountability. Based on this premise, the focus of this study is directed toward two main legal issues related to investment governance in Bali Province: (1) How can a juridical perspective help in understanding the weakness of State Administrative Law as a trigger for corruption in Indonesia? and (2) What solutions can be proposed to address the weaknesses in State Administrative Law in order to prevent corruption in Indonesia? This study is doctrinal in nature and utilizes primary, secondary, and tertiary legal materials. The data collection technique involves the card system and employs a statutory approach, factual approach, and conceptual analysis approach. The findings of this research indicate that juridical approaches to combating corruption should not be limited to repressive measures or sanctions but must also include preventive and corrective strategies. This includes reforming the structure of administrative law, optimizing oversight mechanisms, and integrating administrative law principles into all aspects of government administration. Systemic efforts to strengthen State Administrative Law as part of an anti-corruption strategy must be implemented collaboratively and sustainably. These efforts include regulatory reform, institutional restructuring, and the reinforcement of integrity values and transparency principles in the execution of governmental functions.